2013
DOI: 10.2139/ssrn.2276482
|View full text |Cite
|
Sign up to set email alerts
|

Social Foundations of the Internet in China and the New Internet World: A Cross-National Comparative Perspective

Abstract: This paper provides evidence from survey research on the evolving attitudes, values, and patterns of use defining the New Internet World (NIW). The analysis focuses on China and other 'emerging nations' with similarly strong patterns of Internet diffusion, in comparison with the US and other nations that led the early development of the Internet. These findings lend support to previous research showing that new Internet users across the globe often share fundamental values and beliefs with users in more establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…A decade later, Evgeny Morozov (2012) would discuss the Chinese case as establishing how the Internet could enable greater state surveillance of citizens, due to the ‘traces’ left by online communication, challenging what he referred to as ‘the Net delusion’ of social media as a democratizing force. As China is now by far the world’s largest Internet-using nation, with over 500 million people online – more than double the number of the second largest Internet-using nation, the United States – there is clearly a need to rethink assumptions about the Internet as a force for global liberal democracy (Bolsover et al, 2013). The recurring difficulties that Google has faced operating in China are also indicative of the very different nature of the relationship between state agencies and corporations that prevails in the Chinese context as compared to the United States.…”
Section: Media Systems and The Analysis Of Global Phenomena: The Case Of Internet Policiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A decade later, Evgeny Morozov (2012) would discuss the Chinese case as establishing how the Internet could enable greater state surveillance of citizens, due to the ‘traces’ left by online communication, challenging what he referred to as ‘the Net delusion’ of social media as a democratizing force. As China is now by far the world’s largest Internet-using nation, with over 500 million people online – more than double the number of the second largest Internet-using nation, the United States – there is clearly a need to rethink assumptions about the Internet as a force for global liberal democracy (Bolsover et al, 2013). The recurring difficulties that Google has faced operating in China are also indicative of the very different nature of the relationship between state agencies and corporations that prevails in the Chinese context as compared to the United States.…”
Section: Media Systems and The Analysis Of Global Phenomena: The Case Of Internet Policiesmentioning
confidence: 99%
“…Companies such as Tencent, Alibaba, and Baidu have come to dominate the Chinese Internet market even when they have faced strong competition from Google, Microsoft, Paypal, Yahoo!, and others, as they have been consistently more responsive to specific developments in Internet use in China, in ways that are far more difficult for a Chinese subsidiary of a Western company to achieve. The Oxford Internet Institute survey of worldwide Internet use found that Chinese Internet users were more than twice as likely as US users to make online purchases (59% compared to 23%) and watch videos (85% to 39%) and three times as likely to download music online (80% compared to 19%) (Bolsover et al, 2013: 12). The differences they reported for the use of mobile phone (mobile Internet) to make purchases, watch videos, and download music in China as compared to the United States were even starker.…”
Section: Media Systems and The Analysis Of Global Phenomena: The Case Of Internet Policiesmentioning
confidence: 99%
“…Microblogs can be seen as part of the historical development of the rise of user-generated content since 2005 (Liao, 2014). A recent survey has shown that usergenerated content is more popular in Asia than in the West (Bolsover et al, 2013).…”
Section: Microblog Postsmentioning
confidence: 99%
“…For example, a recent crosscultural survey found that Chinese online users are extremely engaged in commercial and political content. Their online activities dramatically differ from users' activities in Western industrialized countries (Bolsover, Dutton, Law & Dutta, 2013). To understand such unique phenomena, it is imperative to study social media from both the original social context and the global background.…”
Section: Social Media As a Ritual Fieldmentioning
confidence: 99%